2015
DOI: 10.1007/s00068-015-0535-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in medical education: listening to the echoes of the past to shape a vision for the future

Abstract: learners prefer blended learning where material can be reviewed online and personalize the education on their own time frame. This material combined with hands-on experience and mentorship can be used to develop learners' aptitude in ultrasound. Conclusions As educators embrace this ultrasound technology and integrate it throughout the medical education journey, collaboration across specialties will synthesize a clear path forward when needs and resources are paired with vision and a strategic plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…In recent years, there has been a shift toward clinicians performing scans themselves in an attempt to optimize efficiency of patient care and improve safety which has been enabled by falling costs of equipment and the improved usability of machines. The traditional focus of this type of "point of care" US often referred to as POCUS has been largely directed toward emergency medicine and cardiology (Moore and Copel 2011;Lane et al 2015) but increasingly it has also been applied to non-acute specialties, such as rheumatology (Sudoł-Szopi nska et al 2017). It is now commonplace to see machines in or in close proximity to most hospital out-patient and ward facilities to enable these applications.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a shift toward clinicians performing scans themselves in an attempt to optimize efficiency of patient care and improve safety which has been enabled by falling costs of equipment and the improved usability of machines. The traditional focus of this type of "point of care" US often referred to as POCUS has been largely directed toward emergency medicine and cardiology (Moore and Copel 2011;Lane et al 2015) but increasingly it has also been applied to non-acute specialties, such as rheumatology (Sudoł-Szopi nska et al 2017). It is now commonplace to see machines in or in close proximity to most hospital out-patient and ward facilities to enable these applications.…”
Section: Introductionmentioning
confidence: 99%
“…The use of point‐of‐care ultrasound (POCUS) by clinicians has expanded over recent years, accompanied by a growing interest in the use of ultrasound in medical education . Ultrasound is now being used to teach anatomy and physiology, to augment trainees’ clinical evaluation of patients and to assist with procedural guidance . To advocates of further integration of ultrasound in medical education, ultrasound presents an ‘opportunity to revolutionize the way we see and examine patients’ and has become ‘a versatile and essential tool within the field of medicine’ .…”
Section: Introductionmentioning
confidence: 99%
“…We believe that simulation‐based procedural skill laboratories are excellent opportunities to introduce basic concepts of ultrasound. Several authors have demonstrated that early exposure to ultrasound leads to improved understanding of the interplay between anatomy and physiology, improved physical examination skills, and enhanced overall basic science knowledge . Additionally, early ultrasound exposure coupled with a longitudinal learning experience has been shown to optimize skill development and retention, as well as foster an interest in advanced ultrasound training …”
mentioning
confidence: 99%